ABUNDANCE AND DISTRIBUTION OF ZOOPLANKTONS SPECIES IN TUDUN KUKA RIVER KUMO AKKO, GOMBE STATE - MUHAMMAD, KABIRU; SAIDU, HARUNA; DEBA, ABDULKARIMALI; ISAH, ZAINAB; MUHAMMAD, MUHAMMAD AL-AMIN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Management of water resources is of paramount importance especially in rural area facing problems such as lack of access to clean water. Most identifiable sources of water to such areas are mainly rivers and are reported to have serious pollution due anthropogenic activities. Samples of Zooplankton species were collected from Tudun-kuka River using plankton net according to the five minute kicking techniques. Results of Zooplankton analysis shows that total of 165 individuals species were identified, belonging to five (5) different taxa throughout the study period. Out of their total number, Malacostraca has the highest number of species (4) which constituting (40%) of the overall taxa, Actinopterygii and Hexanauplia both has (2) number of species which constitute about (20%) each of them, Polychaeta and Insecta each possess (2) number of Species which constitute about (10%). Physicochemical parameters measured include temperature, turbidity, conductivity and nitrate and they were measured using standard method as recommended APHA. The results indicated that the highest water temperature was recorded at 31°C during July period (month) at site C. For September period, low amount of Temperature of 28°C was measured in site A. For the period of July, highest and lowest water pH of 8.6 and 7.5 was observed at site C and all the three sites (A, B and C) accordingly. Highest turbidity value 11.0 cm was observed in the month of September at site A and the lowest 7.5cm in the month of July at site C. Results of Dissolve Oxygen was found at ranges between 2.70-1.7 mg/L during the period of August plus September at site C. Similarly, the phosphate values were recorded were at ranges of 38.5-33.5 mg/L during the period of July and August at side C. Findings of this research could be useful in generating checklist of zooplankton species found at the river.